Gambaran Variasi Gaya Mengajar Pendidik di Taman Pendidikan Al-Qur’an Raudhatul Islam Kabupaten Padang Pariaman - Deni Marlina; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research was motivated by the phenomenon of the success of the Raudhatul Islam TPA Nagari Toboh Gadang Timur institution in Padang Pariaman Regency. This is evidenced by the large number of students and the many achievements obtained by Raudhatul Islam TPA students. Researchers suspect that the cause of the success of this TPA is because the teaching style of instructors varies in learning activities. This type of research is quantitative descriptive research. The population in this study were 180 students of Raudhatul Islam Landfill. Samples are taken with the intention or purpose of as many as 45 people. Data analysis techniques use a percentage formula. The results showed that the variation of educator teaching style was seen from the aspect of sound variation, concentration of students' attention, changes in the position of educators and made contact with students when learning activities were categorized as good.Keywords: Variation, Teaching Style, Educator